Butyrate limits the replication of porcine epidemic diarrhea virus in intestine epithelial cells by enhancing GPR43-mediated IFN-III production - He, Haiyan; Fan, Xuelei; Shen, Haiyan; Gou, Hongchao; Zhang, Chunhong; Liu, Zhicheng; Zhang, Bin; Wuri, Nile; Zhang, Jianfeng; Liao, Ming; Geri, Letu (Frontiers in Microbiology, 2023)
Porcine epidemic diarrhea virus (PEDV) is a threat to the health of newborn piglets and has a significant impact on the swine industry. Short-chain fatty acids (SCFAs) are gut microbial metabolites that regulate intestinal function through different mechanisms to enhance the intestinal barrier and immune function. In this study, we aimed to determine whether butyrate displayed a better effect than other SCFAs on limiting PEDV replication in porcine intestinal epithelial cells. Mechanistically, butyrate treatment activated the interferon (IFN) response and interferon-stimulated gene (ISG) expression. Further experiments showed that inhibition of GPR43 (free fatty acid receptor 2) in intestinal epithelial cells increased virus infection and reduced antiviral effects through IFN λ response. Our findings revealed that butyrate exerts its antiviral effects by inducing GPR43-mediated IFN production in intestinal epithelial cells.